Evaluasi Pengguna Aplikasi P-Care Vaksinasi dengan Technology Acceptence Model (TAM) di Puskesmas Sewon 2 - Ellisa Pahlevi Ardyagarini; Tri Ariani; Muhammad Muslim (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: The P-Care Vaccination application is an application used to make it easier for officers to verify vaccination participant data and to assist the government in monitoring vaccination implementation in real time and obtaining valid vaccination data. The P-Care Vaccination application has several features including the vaccination target feature, vaccination entry and vaccination monitoring which often experience problems in its use. The problems that often arise are usually P-care cannot find NIK data on the Care Protect and Dukcapil applications and the same ticket number has been used by another NIK (double ticket case) in the vaccination entry feature and problems with the application users themselves. Objective: To evaluate user experience in using the P-Care Vaccination application at the Sewon II Community Health Center. Method: The research used was qualitative descriptive. Results: Based on the results of user evaluation of the P-Care Vaccination application using five evaluation criteria in the TAM method, the results obtained were: 1) Perceived usefulness of 10 users who felt the application was useful. 2) Perception of ease of use (acceptance of IT) 8 officers felt the application was easy to use, 2 officers felt the application was difficult to use. 3) Desire to use (attitude toward) 10 officers considered the features and menus easy to understand. 4) Attitudes towards use (behavioral intention of use) of 10 officers felt that the application often experienced errors and loading. 5) Actual system use: 10 officers said they actually used the system. Conclusion: Based on the evaluation results of 5 aspects, the lowest aspect occurs in the aspect of ease of use of the application. Keywords: Evaluation, Application, P-care Vaccination, TAM.